The Effect of Training and Job Placement on Employee Performance at PT Adis Dimension Footwear Sewing Division NCVS 1.03 in Tangerang Regency - Nurhidayat, Deden; Soebadio, Bizzma Buana Amriki; Umam, Akhmad Hairul (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The purpose of this study was to determine how much influence job training and job placement have on employee performance at PT. Adis Dimension Footwear, Sewing NCVS 1.03, Tangerang Regency. This study uses a quantitative descriptive method. The population in this study were all employees at PT Adis Dimension Footwear, Sewing NCVS 1.03, Tangerang Regency. The research sample consisted of 68 respondents.The results of this study indicate that (1) partially, job training significantly influences employee performance at PT. Adis Dimension Footwear Sewing NCVS 1.03 Tangerang Regency, as indicated by the calculated t value > t table (4.528 > 1.997) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, job placement significantly influences employee performance at PT. Adis Dimension Footwear Sewing NCVS 1.03 Tangerang Regency, as indicated by the calculated t value > t table (2.713 > 1.997) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, job training and job placement significantly influence employee performance at PT. Adis Dimension Footwear Sewing NCVS 1.03 Tangerang Regency, which is indicated by Fcount> Ftable (97.176> 3.14) with a significance level of 0.000, thus Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the variables of work stress and work discipline, both partially and simultaneously, have a significant influence on employee performance at PT. Adis Dimension Footwear Sewing NCVS1.03 Tangerang Regency.